2021
DOI: 10.1186/s13104-021-05750-1
|View full text |Cite
|
Sign up to set email alerts
|

DArT-based evaluation of soybean germplasm from Polish Gene Bank

Abstract: Objective Soybean is an important plant used for food, feed and many industrial purposes. Interest in soybean breeding is growing in Central Europe, including Poland. A very large number of soybean accessions are stored in gene banks, but less than 1% of them have been used for breeding. Here, we present genotypic data as well as phenotypic data on plant and seed performance, including seed chlorophyll fluorescence traits, and on yield components within a collection of soybean accessions that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In case of barley (Hordium vulgare), rusts and PM diseases that have a major effect on yield. Based on phenotyping of 431 European barley accessions for two seasons and genotyping using DArT-seq, 78 MTAs for PM and rusts adult plant resistance were reported (Czembor et al, 2022). In case of spot blotch resistance, 11 out of 20 genetic loci at the seedling and adult stages were associated with functional candidate genes.…”
Section: Barleymentioning
confidence: 99%
“…In case of barley (Hordium vulgare), rusts and PM diseases that have a major effect on yield. Based on phenotyping of 431 European barley accessions for two seasons and genotyping using DArT-seq, 78 MTAs for PM and rusts adult plant resistance were reported (Czembor et al, 2022). In case of spot blotch resistance, 11 out of 20 genetic loci at the seedling and adult stages were associated with functional candidate genes.…”
Section: Barleymentioning
confidence: 99%
“…The DArT data were handled in the same manner as described previously for soybean [61]. That is, we used the dartR v1.1.11 package [62] in the R programming language.…”
Section: Data Filtering Processmentioning
confidence: 99%
“…In Europe, early maturity soybean accessions from the north of Europe are related to chilling tolerant plant introductions similar to Canadian genotypes (Yamaguchi et al 2018), whereas south European soybeans frequently have a northern United States (US) genetic background (Hrustic and Miladinovic 2011;Tomicic et al 2015). Genetic diversity in French (Tavaud-Pirra et al 2009), Polish (Czembor et al 2021), Central European (Hahn and Würschum 2014) and Central-South European (Žulj Mihaljević et al 2020) soybean germplasm and breeding materials has been reported in a number of individual studies utilizing different genomic tools and marker systems, but a comprehensive European analysis is still missing.…”
Section: Introductionmentioning
confidence: 99%